Oxytetracycline accumulation in the macroalgae Ulva: Potential risks for IMTA systems - Rosa, João (2019)
Oxytetracycline (OTC) is one of the most used antibiotics in aquaculture. With the development of Integrated Multitrophic Aquaculture (IMTA) systems in order to mitigate some aquacultures' adverse effects, attention needs to be shifted to other co-cultured species that can also accumulate such pharmaceuticals and pose a risk to human consumption. Therefore, the present work evaluated the exposure of the seaweed Ulva to OTC at two realistic concentrations (0.040 and 0.120 mg L1 ). Oxytetracycline degradation rates in seawater were dependent on the initial concentration but were not influenced by the presence of Ulva. The macroalgae presented good assimilation rates of OTC, with internal concentrations reaching 40.9934 ng g1 WW for the lowest concentration tested and 108.6787 ng g1 WW for the highest, with a steep decrease after 48 and 24 h, respectively. Nonetheless, concentrations were still half of the Maximum Residue Limit set for fish (100 mg kg1) 48 h after C2 treatment. The highest dosage tested stimulated growth 96 h after the beginning of the trial, although some signs of decay could also be found in Ulva's fronds.